In varietate concordia. Nauki humanistyczne i ich wpływ na imaginarium społeczne - Żardecka, Magdalena (Tematy i Konteksty, 2019)
The paper views human sciences as a kind of cultural bond, building unity across all divisions and boundaries. For this purpose it uses arguments proposed by such intellectuals as Nussbaum, Rorty, Markowski and Assmann. It aims at justification of the thesis that humanities serve intrinsic integration and development of personality, social integration, maintaining bonds with the past and history, and creating a sense of common destiny of all human beings. Human sciences expand our horizons, allowing us to transcend the limits of our inborn egoism, they teach us how to imaginatively reach beyond and above the local perspective, creating foundations for interpersonal solidarity, respect, tolerance and compassion. The present political trends in Poland and in the world clearly favor natural and technical sciences, tending to devaluate and to marginalize humanities, which can be a prognostic of cultural regress, with unpredictable consequences for the future.